Body size, socioeconomic status and training background of a select group of U16 South African rugby union players (2010-2013): The impact on national selection - Arkell, Robin (MRC/UCT RU for Exercise and Sport Medicine, 2016)
Background: Rugby Union is an international sport characterized by bouts of short duration, high intensity exercise in which players frequently collide into one another while running at high speeds. Players are commonly required to engage in phases of play involving contact such as tackling, rucking, mauling and scrumming. These phases of play require certain physical qualities, including strength, aerobic power, speed and explosive power. Perhaps, the growth and professionalization of the game has resulted in more emphasis being placed on the physical preparation of the players. Physical preparation of players not only happens at elite senior levels, but has also filtered down into the junior ranks, where it is common for school teams to be trained by professional strength and conditioning coaches. The rules of the game have changed, which have influenced the physical demands. For example, ball-in-play time has increased, players are covering more distance per game, making more tackles and engaging in more scrums. It is therefore important to identify the various physical characteristics that are required to be successful at a particular level of rugby union. The socioeconomic status and ethnicity of the player in association with the physical characteristics can determine the success of an adolescent rugby player. Objective: To determine the association between body mass and stature (referred to as physical characteristics for this study), race, socioeconomic status, and weight training (referred to as non-physical characteristics for this study) on the chances of success among U16 provincial rugby union players. In particular, size, socioeconomic status and ethnicity of players in the U16 national training squad were compared to players who represented their provinces but did not get selected for the national squad. Methods: Data were collected for each player who attended the Coca Cola National Grant Khomo week from 2010 to 2013. Players participating in this tournament had already undergone a process of selection trials to be selected to represent their province at U16 level. The national squad players were chosen based on performances at the Coca Cola National Grant Khomo week. The characteristics of the players selected for the national squad vs. players who did not get selected for the squad from 2010 to 2013 were compared using an ANOVA and the magnitude of the differences were quantified using effects sizes. Results: White players are heavier (ES = 0.59) and taller (ES = 0.8 2) than black players as well as heavier (ES = 0.8 7) and taller (ES = 0.8 2) than coloured players over the four-year period from 2010 to 2013. Players selected into the National squad were on average heavier (ES = 0.5 0) and taller (ES = 0.4 0) than those players not selected into the National squad. White players were the heaviest and tallest of the race groups selected into the National squad (p < 0.0000 2). Players with a high socioeconomic status were heavier (ES = 0.3 0), taller (ES = 0.4 0), and had more playing experience (ES = 0.3 0), than players from a low socioeconomic status background. Grouping according to socioeconomic status did not differentiate between race groups and selection for the national squad. Conclusion: This study showed that the taller and heavier players were more likely to get selected for the national U 16 squad. Since size was also associated with socioeconomic status, the players with a high socioeconomic status had an advantage over players with a low socioeconomic status. These findings have implications for transforming the game to ensure that the representative teams reflect the composition of the South African population.